Increase of high sensitivity cardiac troponin I and NT-proBNP in competitive athletes after a 50-km ultramarathon race: physiological adaptation or myocardial injury? - Perrone, M. A.; Pieri, M.; Minnucci, M.; Salimei, C.; Ciminelli, E.; Bernardini, S.; Iellamo, F. (Medicina dello Sport, 2023)
BACKGROUND: High-sensitivity cardiac troponins I (hs-cTnI) and T (hs-cTnT) and natriuretic peptides (BNP and NT-proBNP) are universally recognized as reference cardiac biomarkers in patients with acute coronary syndromes and heart failure, respectively. Recent studies have shown that these biomarkers can be increased even in healthy competitive athletes after intense and prolonged physical exercise. However, it is not yet clear whether the increase in these cardiac-specific biomarkers should be considered a normal physiological adaptation to physical exercise or a real myocardial injury. The aim of this study was to evaluate hs-cTnI and NT-proBNP levels in healthy competitive athletes before and after a 50-km ultramarathon.